Indicators Of Land Rights Certificate Cancellation Caused By Overlapping Rights As Administration Failure - Suhani Wulandari (Fakultas Hukum Universitas Lampung, 2020)
Land registration which aims to provide legal certainty for the ownership of a person's land parcel, which is in the form of a certificate of land title, in the issuance of which there may be errors resulting in two certificates or overlapping so that one certificate can be ascertained that it contains administrative defects, in handling the dispute case settlement refers to the Regulation of the Minister of ATR/KaBPN Number 11 of 2016 article 24 paragraph (7).This study aims to determine, land title certificate can be said to be administratively flawed, Implementation of cancellation of land title certificate due to administrative defect errors at the Regional Office of BPN Lampung Province and the Land Office. This research uses empirical normative juridical research method. The research approach uses a statutory, analytical and participatory approach. Data analysis uses primary and secondary data to draw conclusions using inductive logic. The results show that in order to resolve dispute cases with an overlapping typology of land title certificates, it is necessary to cancel one of the certificates issued in the latest year, because it can be ascertained that it contains errors in its issuance so that it becomes an administrative defect. And tthe cancellation of the certificate of land title is carried out on the basis of a public complaint or BPN initiative, with a request submitted by the Land Office, the Land Office carries out data collection activities, analysis accompanied by Case Handling Progress Report to be submitted to the Regional Office, at the Regional Office Assessment, Field Research, Exposure, Case Settlement Reports and the issuance of a Decree on the Cancellation are then submitted to the Land Office for announcement and deletion in the Land Office data base.